Analisis Penggunaan Internet Sehat Pada Kalangan Masyarakat Desa Sigara-Gara - Ivena Hotmarina Septiani Nainggolan; Yaumil Hasanah Siagian; Retno Puspita Dewi; Suci Faddillah; Muhammad Dary Daffa Haque; Franindya Purwaningtyas (Universitas Batanghari Jambi, 2022)
The internet is something that people use the most every day. The dominant internet users come from groups of teenagers or students. It is often found that individuals who abuse the internet need to be educated on how to surf the internet in a healthy way. Healthy Internet is a program from the Indonesian government designed by the Indonesian Ministry of Communication and Information (Kemkominfo). The purpose of this study was to find out how healthy internet usage is among the people of Sigara-gara Village. The research method used is qualitative descriptive, the number of samples is 48 respondents. The analysis used is univariate analysis and Cartesian diagram. This research was conducted in Sigara-gara Village, Patmbak District, Deli Serdang Regency. The result of this research is that it is found that the people of Sigara-gara village are still not good at using the internet in their daily life as evidenced by the survey results as many as 48 respondents out of 240 people have used the internet. Around 40.8% of 80% of the Sigara Village Community work as entrepreneurs.